Circulating plasma cells in newly diagnosed symptomatic multiple myeloma as a possible prognostic marker for patients with standard‐risk cytogenetics. (26th May 2015) - Vagnoni, Davide; Travaglini, Fosco; Pezzoni, Valerio; Ruggieri, Miriana; Bigazzi, Catia; Dalsass, Alessia; Mestichelli, Francesca; Troiani, Emanuela; Falcioni, Sadia; Mazzotta, Serena; Natale, Annalisa; Angelini, Mario; et al.
Summary Detection of circulating plasma cells (PCs) in multiple myeloma (MM) patients is a well‐known prognostic factor. We evaluated circulating PCs by flow cytometry (FC) in 104 patients with active MM at diagnosis by gating on CD38+ CD45‐cells and examined their relationship with cytogenetic risk. Patients had an average follow‐up of 36 months. By using a receiver operating characteristics analysis, we estimated the optimal cut‐off of circulating PCs for defining poor prognosis to be 41. Patients with high‐risk cytogenetics (n = 24) had poor prognosis, independently of circulating PC levels [PC < 41 vs. PC ≥ 41: overall survival (OS) = 0% vs. OS = 17%, P = not significant (n.s.); progression‐free survival (PFS) = 0% vs. 17%, P = n.s.]. Patients with standard‐risk cytogenetics (n = 65) showed a better prognosis when associated with a lower number of circulating PCs (PC < 41 vs. PC ≥ 41: OS = 62% vs. 24%, P = 0·008; PFS = 48% vs. 21%, P = 0·001). Multivariate analysis on the subgroup with standard‐risk cytogenetics confirmed that the co‐presence of circulating PCs ≥ 41, older age, Durie‐Salmon stage >I and lack of maintenance adversely affected PFS, while OS was adversely affected only by lactate dehydrogenase, older age and lack of maintenance. Our results indicate that the quantification of circulating PCs by a simple two‐colour FC analysis can provide useful prognostic information in newly diagnosed MM patients with standard‐risk cytogenetics.